2021
DOI: 10.19182/bft2021.349.a36776
|View full text |Cite
|
Sign up to set email alerts
|

Variations des caractéristiques physiques et mécaniques du bois de Balanites aegyptiaca en fonction de trois provenances

Abstract: Balanites aegyptiaca est une espèce caractéristique et emblématique des zones sèches d’Afrique et d’Asie. Elle revêt une grande importance socio-économique dans toute sa zone naturelle de répartition du fait de ses multiples usages. Toutefois, les propriétés technologiques de son bois sont mal connues, d’où des utilisations parfois inappropriées mais qui pourraient être élargies. Afin de mieux adapter ses applications à ses caractéristiques, nous avons déterminé les indicateurs de stabilité physique (masse vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[12,14] B.aegyptiaca kernel oil has been found to possess exceptional antioxidant, anti-inflammatory, and antiviral properties. [15,16] Nonetheless, the phytochemical composition of B. aegyptiaca varies among different countries, exhibiting diverse profiles and antioxidant activities. For example, a study conducted on the fruit of thirty individual trees in Mauritania revealed significant diversity in the fruit's phytochemicals and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14] B.aegyptiaca kernel oil has been found to possess exceptional antioxidant, anti-inflammatory, and antiviral properties. [15,16] Nonetheless, the phytochemical composition of B. aegyptiaca varies among different countries, exhibiting diverse profiles and antioxidant activities. For example, a study conducted on the fruit of thirty individual trees in Mauritania revealed significant diversity in the fruit's phytochemicals and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%